Substance Abuse Treatment Centers and Local Crime - Samuel R. Bondurant; Jason M. Lindo; Isaac D. Swensen (Institute for the Study of Labor (IZA), 2016)
In this paper we estimate the effects of expanding access to substance-abuse treatment on local crime. We do so using an identification strategy that leverages variation driven by substance-abuse-treatment facility openings and closings measured at the county level. The results indicate that substance-abuse-treatment facilities reduce both violent and financially motivated crimes in an area, and that the effects are particularly pronounced for relatively serious crimes. The effects on homicides are documented across three sources of homicide data.
Keywords: I12; K14; K42; 330; substance abuse treatment; crime; homicides